2015
DOI: 10.3892/ol.2015.3218
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the PI3K/Akt signaling pathway affects cell cycle and apoptosis of side population cells in nasopharyngeal carcinoma

Abstract: Abstract.Increasing evidence has suggested that certain types of cancer possess their own stem-like cells, and that one subset of these cells, termed the side population (SP), may have an important role in tumorigenesis and cancer therapy. However, the molecular mechanisms underlying the modulation of SP cells in nasopharyngeal carcinoma (NPC) have remained elusive. In the present study, it was hypothesized that dysregulation of the phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K)/Akt signaling pathway ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…8,9) Additionally, AKT inactivates Bad and caspase-9, two pro-apoptotic proteins, 13) whereas inhibition of AKT signaling induces cell death by reducing the expression of Bcl-2 and enhancing the expression of Bax or Bad. 14) Our results show that QI treatment decreased the TP-induced activation of AKT and GSK3β. We also found that these QI-induced decreases in p-AKT and p-GSK3β levels paralleled reduced cyclin D1 expression and a decrease in the Bcl-2/Bax ratio.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…8,9) Additionally, AKT inactivates Bad and caspase-9, two pro-apoptotic proteins, 13) whereas inhibition of AKT signaling induces cell death by reducing the expression of Bcl-2 and enhancing the expression of Bax or Bad. 14) Our results show that QI treatment decreased the TP-induced activation of AKT and GSK3β. We also found that these QI-induced decreases in p-AKT and p-GSK3β levels paralleled reduced cyclin D1 expression and a decrease in the Bcl-2/Bax ratio.…”
Section: Discussionmentioning
confidence: 48%
“…8,9,13,14) Quisqualis indica (QI), commonly known as Chinese honeysuckle or Rangoon creeper, is a vine of the Combretaceae family that grows in tropical Asian countries, such as China, the Philippines, Bangladesh, Myanmar, India, and Malaysia.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that inhibition of the PI3K/Akt pathway can induce cell death[30]. Phosphorylated Akt functions as a survival signal partially by inactivating two pro-apoptotic proteins, Bad and caspase-9[31].…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K (phosphoinositide 3-kinase)/Akt signaling pathway is a major driving force in a variety of cellular functions. Dysregulation of this pathway has been implicated in many human diseases including cancer (9)(10)(11)(12). Therapy resistance is critical to tumor maintenance and severely limits Fra-1 is upregulated in gastric cancer tissues and affects the PI3K/Akt and p53 signaling pathway in gastric cancer cancer patient survival.…”
Section: Introductionmentioning
confidence: 99%